Oral Lesion as Unusual First Manifestation of Multiple Myeloma: Case Reports and Review of the Literature. (24th November 2014) - Romano, A.; Marescalco, M. S.; Liardo, Chiara; Villari, L.; Vetro, C.; Conticello, C.; Di Raimondo, F.; Ferlito, S.
Abstract : Extramedullary plasmacytoma (EMP) and solitary bone plasmacytoma (SBP) represent a disease continuum through a multistage process of cell differentiation, survival, proliferation, and dissemination, strictly related to multiple myeloma (MM), the second most common hematological malignancy. Herein, we report two cases of recurrent oral plasmacytoma progressed to MM, in which the first clinical sign of a more widespread disease was limited to the mouth. Based on our experience, we recommend a strict workup for the differential diagnosis between EMP, SBP, and MM for patients with oral plasmacytoma, including radiological exam of the skeleton, magnetic resonance imaging (MRI) of the bone, and positive emission tomography (FDG-PET). MRI and possibly PET can all be used to more sensitively detect EM plasmacytoma sites.